Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Matematika Siswa Kelas IV SD Mutiara Bali - Mentari Anggraini; Zulqoidi R. Habibie (Master of Pedagogy and Elementary School Learning, 2026)
The low mathematics learning outcomes of elementary school students remain one of the challenges in improving educational quality. This condition is often caused by the use of teacher-centered learning models that limit student participation during the learning process. Therefore, innovative learning approaches are needed to improve students' understanding and achievement in mathematics. This study aimed to determine the effect of the Problem Based Learning (PBL) model on the mathematics learning outcomes of fourth-grade students at SD Mutiara Bali. The research employed a quantitative approach with a quasi-experimental design. The population consisted of 26 fourth-grade students, comprising 15 female students and 11 male students. The sampling technique used was saturated sampling, in which all members of the population were selected as the research sample. Data were collected through learning outcome tests and observations. The collected data were analyzed using descriptive and inferential statistical techniques. The results showed that the average pretest score was 63.27, while the average posttest score increased to 82.12. The increase of 18.85 points indicates an improvement in students’ mathematics learning outcomes after the implementation of the Problem Based Learning model. Furthermore, the N-Gain score was 0.51, which falls into the moderate category. These findings indicate that the Problem Based Learning model has a positive effect on students' mathematics learning outcomes and can be used as an effective learning alternative in elementary schools.